Persistent lactic acidosis in neonatal hypoxic–ischaemic encephalopathy correlates with EEG grade and electrographic seizure burden. Issue 3 (28th November 2006) - Murray, D M; Boylan, G B; Fitzgerald, A P; Ryan, C A; Murphy, B P; Connolly, S
Abstract : Background: Predicting at birth which infants with perinatal hypoxic–ischaemic injury will progress to significant encephalopathy remains a challenge. Objective: To determine whether lactic acidosis at birth in asphyxiated neonates could predict the grade of EEG encephalopathy by examining the relationship between time taken for the normalisation of lactate, severity of encephalopathy and seizure burden. Methods: Continuous early video-EEG monitoring was performed in babies at risk for hypoxic–ischaemic encephalopathy. Encephalopathy was graded from the EEG data. Total seizure burden (seconds) was calculated for each baby. Initial blood gas measurements of pH, base deficit and lactate were taken within 30 minutes of delivery. Time to normal serum lactate was determined in hours from birth for each infant. Results: All 50 term infants had raised initial serum lactate (median (lower, upper quartiles) 11.7 (10.2, 14.9)). There were no significant differences between the initial serum lactate, pH and base deficit in infants with normal/mildly abnormal (n = 24), moderately abnormal (n = 14), severely abnormal (n = 5) and inactive EEGs (n = 7). Time to normal lactate varied significantly with EEG grade (median (lower, upper quartile) 6.0 (4.1, 9.5) for mild/normal EEG, 13.5 (6.8, 23.5) moderate EEG, 41.5 (30.0, 55.5) severe group, 12.0 (8.1, 21.5) inactive group; p<0.001). Time to normal lactate correlated significantly with EEG seizure burden (seconds; R = 0.446, p = 0.002). Mean (SD) time to normal lactate was 10.0 (7.2) hours in infants who did not have seizures and 27.3 (19.0) hours in the 13 infants with electrographic seizures (p = 0.002). Conclusions: Serum lactate levels in the first 30 minutes of life do not predict the severity of the ensuing encephalopathy. In contrast, sustained lactic acidosis is associated with severe encephalopathy on EEG and correlates with seizure burden.